THE EFFECT OF GOVERNMENT SPENDING ON ECONOMIC GROWTH - Ashraf Turdialiev; Shokhzod Khujamurotov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Government spending plays a pivotal role in shaping the economic trajectory of a nation. As a key instrument of fiscal policy, it influences both short-term economic stability and long-term development outcomes. This article explores the multifaceted relationship between government spending and economic growth, drawing on theoretical frameworks, empirical evidence, and international case studies. It begins by categorizing government expenditures into capital and current spending, analyzing how each type contributes differently to economic performance. Capital investments—such as in infrastructure, education, and healthcare—are shown to have stronger and more sustainable impacts on productivity and growth potential. In contrast, current expenditures often yield more immediate but less enduring benefits. The paper reviews classical economic theories, contrasting Keynesian advocacy for expansionary government spending with neoclassical concerns over potential crowding-out effects on private investment. Through empirical examples from both developed and developing economies, the article highlights how the impact of government spending is highly context-dependent, varying according to institutional quality, fiscal discipline, and strategic allocation. Case studies, including China's infrastructure-led growth model and Greece's fiscal crisis, illustrate the dual nature of government spending as either a catalyst for development or a source of macroeconomic imbalance. Furthermore, the article addresses the risks associated with excessive or inefficient government spending, such as rising public debt, inflationary pressures, and resource misallocation.